Genotoxic and hematological effects of aluminium and lead exposure in red hybrid tilapia (Oreochromis sp.) / Faten Fatehah Mohamad Zaid - Faten Fatehah , Mohamad Zaid (2020)

(untitled)
This study was conducted to investigate the genotoxic effects of single aluminium (Al), 25.00 mg/l, single lead (Pb), 18.75 mg/l and binary mixtures of Al and Pb (25.00 mg/l + 18.75 mg/l) and to determine their hematological effects on the tilapia fish as test subjects after 96 h exposure to these heavy metals. Oreochromis sp. was selected as the test subjects because of its adaptability to the environment and it can be easily found as it is the most common species of freshwater fish being cultured and farmed. Two different methods, micronucleus test and comet assay, were used for the genotoxicity studies while complete blood count (CBC) test was used for the hematological studies. Results showed that 18.75 mg/l of Pb was able to significantly induce the highest erythrocytes with nuclear abnormalities and highest erythrocytes with comets compared to the other samples. Regarding the absolute blood measurement index, it could be seen that there were significant differences in red blood cell (RBC) which is 0.000 and white blood cells (WBC), 0.010, which is (p<0.05) of Pb at 18.75 mg/l compared to the other samples and control. This study showed that the micronucleus test, comet assay test and complete blood count test were able to support the results of the genotoxic and hematology study whereby Pb created a bigger impact on the samples compared to Al and the mixtures of Al and Pb. In addition, this study strengthen the different methods as complementary to each other in assessing the effects of genotoxicity and the hematological effects of Oreochromis sp. exposed to heavy metals of Al and Pb.